2021
DOI: 10.1002/ajmg.a.62509
|View full text |Cite
|
Sign up to set email alerts
|

Novel hemizygous loss‐of‐function variant in NONO identified in a South African boy

Abstract: Hemizygous loss-of-function variants in the non-POU domain-containing, octamerbinding gene, NONO, cause X-linked mental retardation syndrome 34 (MRXS34).Here, we describe the 12th patient in the literature with this rare syndrome, the first affected male from sub-Saharan Africa. This South African patient presented with dysmorphic features, congenital cardiac abnormalities (Ebstein's anomaly, left ventricular non-compaction, and a VSD), and developmental delay. He was enrolled in our "Undiagnosed Disease Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…LVNC was the most common cardiac phenotype. We also found that LVNC is diagnosed early in almost all individuals (Table 1): six individuals who were pregnant, including the fetus we reported[6], four individuals who were in the neonatal period [3,5], and three individuals who were in infancy [2,4,9], indicating that LVNC is an early clue for diagnosing MRXS34 and emphasizing the importance of fetal echocardiography for identifying cardiac structural anomalies in NONO-related fetuses. impediment, which are characterized phenotypes of MRXS34 [1].…”
Section: Discussionmentioning
confidence: 54%
“…LVNC was the most common cardiac phenotype. We also found that LVNC is diagnosed early in almost all individuals (Table 1): six individuals who were pregnant, including the fetus we reported[6], four individuals who were in the neonatal period [3,5], and three individuals who were in infancy [2,4,9], indicating that LVNC is an early clue for diagnosing MRXS34 and emphasizing the importance of fetal echocardiography for identifying cardiac structural anomalies in NONO-related fetuses. impediment, which are characterized phenotypes of MRXS34 [1].…”
Section: Discussionmentioning
confidence: 54%
“…With roles in almost every step of gene regulation 10 , Nono has diverse molecular functions, and it is gradually founded the clinically relevant in the contexts of cancer 25 , Innate immunity 26 , neurodevelopment 27 . Recently, it is reported worldwide that fifteen cases with cardiac phenotypes of LVNC and CHD have been found NONO loss-of-function variants 11 17 . To this date, there are no reports on the cardiac development of NONO .…”
Section: Discussionmentioning
confidence: 99%
“…As a multifunctional nuclear protein, NONO performs a variety of tasks involved in RNA synthesis, transcriptional activity, post-transcriptional regulation and DNA repair 10 . Emerging clinical evidences 11 17 showed that the loss-of-function variants of NONO could lead to left ventricular non-compaction (LVNC) and CHD, such as atrial septal defect (ASD), ventricular septal defect (VSD), Patent ductus arteriosus (PDA), pulmonary stenosis/pulmonary atresia (PS/PA), Ebstein's anomaly and Hypoplastic left heart syndrome in males. These suggested that NONO deficiency may influence cardiac development and lead to impaired cardiac structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Less clear is the involvement of NONO in heart defects that has been confirmed to be present in the most of NONO -patients. From the first description of a subjects with a pathogenic variant of NONO presenting with LVNC [ 2 ], this cardiac defect was reported in the other 12 male patients, making this clinical feature as a distinctive sign of this disorder [ 2 , 3 , 4 , 5 , 6 , 7 ]. Based on literature review, LVNC was isolated in two cases (2/13; 15%), whereas was reported in association with other structural heart defects in the others (11/13; 85%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that LVNC may be part of this newly described syndrome [ 2 ]. Effectively, since then, 73% of subjects affected by MRXS34 were reported showing cardiac anomalies, in particular LVNC, but also septal defects and right-sided lesions as Ebstein’s anomaly [ 3 , 4 , 5 , 6 ]. Heart defects were also disclosed as the peculiar clinical characteristic of a series of male fetuses with NONO variants detected by WES analysis [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%